2014
DOI: 10.1007/s10753-014-0048-2
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 Inflammasome Activation Is Essential for Paraquat-Induced Acute Lung Injury

Abstract: The innate immune response is important in paraquat-induced acute lung injury, but the exact pathways involved are not elucidated. The objectives of this study were to determine the specific role of the NLRP3 inflammasome in the process. Acute lung injury was induced by administering paraquat (PQ) intraperitoneally. NLRP3 inflammasome including NLRP3, ASC, and caspase-1 mRNA and protein expression in lung tissue and IL-1β and IL-18 levels in BALF were detected at 4, 8, 24, and 72 h after PQ administration in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 39 publications
2
43
1
Order By: Relevance
“…In addition, Samantaray et al 33 have shown that MT inhibited inflammation by suppressing the activation of macrophages, microglia, and astrocytes, thus decreasing the level of axonal degeneration after SCI injury. 38,39 In addition, it was reported that Cd could trigger inflammatory cell death via NLRP3 inflammasomes. These results are consistent with those published by Genovese et al 32 who showed that MT treatment could dramatically improve limb functions by playing strong anti-inflammatory roles in an animal model of SCI.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Samantaray et al 33 have shown that MT inhibited inflammation by suppressing the activation of macrophages, microglia, and astrocytes, thus decreasing the level of axonal degeneration after SCI injury. 38,39 In addition, it was reported that Cd could trigger inflammatory cell death via NLRP3 inflammasomes. These results are consistent with those published by Genovese et al 32 who showed that MT treatment could dramatically improve limb functions by playing strong anti-inflammatory roles in an animal model of SCI.…”
Section: Discussionmentioning
confidence: 99%
“…PQ is a strong pneumotoxicant, particularly due to its ability to accumulate in the lung, which is facilitated by alveolar epithelial cells via the polyamine uptake pathway, resulting in ALI (23). Despite the mechanism underlying the development of lung injury by PQ remaining undetermined, previous studies have demonstrated that oxidative and inflammatory mediators induced by PQ may result in tissue injury (24). Current treatments for PQ poisoning primarily consist of anti-inflammatory and anti-oxidative treatments for the attenuation of PQ-induced ALI (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of ROS production or scavengers of ROS, such as NAD(P) H oxidase inhibitors, can suppress NLRP3 inflammasome activation48. ROS activates NLRP3 inflammasome in paraquat, burn, and hemorrhagic shock-induced ALI104950. It has been reported that TREM-1 activation stimulates intracellular Ca 2+ mobilization11.…”
Section: Discussionmentioning
confidence: 99%